Authentication and anti-duplication security system for Visa and MasterCard card - Meneses Claudio, Brian (2022)
This document attempts to provide the security to make a transaction, with the online transaction authentication flow, in order to make our purchases safely as there are many frauds and little security on the part of users when making an online purchase, as well as identity theft or card duplication, which cause transactions to be less reliable, with this system we will try to give the necessary confidence to make online purchases with our transaction flow, we will also use an agile methodology to design the system, which to develop it we will have to follow a few steps which will be elaborated, by 5 steps to develop this article.